2019
DOI: 10.1002/ange.201909069
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer Solution To Prevent Nanoclustering and Improve the Selectivity of Metal Nanoparticles for Electrocatalytic CO2 Reduction

Abstract: The stability of metal nanocatalysts for electrocatalytic CO2 reduction is of key importance for practical application. We report the use of two polymeric N‐heterocyclic carbenes (NHC) (polydentate and monodentate) to stabilize metal nanocatalysts (Au and Pd) for efficient CO2 electroreduction. Compared with other conventional ligands including thiols and amines, metal–carbene bonds that are stable under reductive potentials prevent the nanoclustering of nanoparticles. Au nanocatalysts modified by polymeric NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…To further confirm the beneficial role played by the NHC polymer on catalysis, an analogous effect was also observed for Pd NPs, which showed an increase in the CO selectivity and stability as compared to commercial Pd/C. 456 In addition to metal NPs, the functionalization of NHCs was recently reported to affect the catalytic properties of polycrystalline metal surfaces. In particular, Pd electrodes modified with tridentate NHC ligands displayed a 32-fold activity enhancement for CO 2 conversion to C 1 products as compared to an unmodified Pd foil, producing HCOO À in high faradaic yields.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…To further confirm the beneficial role played by the NHC polymer on catalysis, an analogous effect was also observed for Pd NPs, which showed an increase in the CO selectivity and stability as compared to commercial Pd/C. 456 In addition to metal NPs, the functionalization of NHCs was recently reported to affect the catalytic properties of polycrystalline metal surfaces. In particular, Pd electrodes modified with tridentate NHC ligands displayed a 32-fold activity enhancement for CO 2 conversion to C 1 products as compared to an unmodified Pd foil, producing HCOO À in high faradaic yields.…”
mentioning
confidence: 77%
“…Recently, the encapsulation of metal NPs into monodentate or polydentate polymeric NHC matrices was explored as an effective strategy to further improve at the same time catalyst selectivity and longterm durability, preventing nanoclustering. 456 The embedded Au NPs exhibited excellent FE CO with a ca. 86% activity retention over 11 h electrolysis under CO 2 atmosphere at À0.9 V vs. RHE, clearly outperforming the bare Au NPs which lost approximately 90% of their initial activity.…”
mentioning
confidence: 99%
“…It has been demonstrated that NHC ligands have the ability to enhance nanocrystal catalyst stability and increase nanocrystal catalyst activity and/or selectivity. [9][10][11][12] NHC-stabilized nanocrystals have been shown to display catalytic activity toward, for example, hydrogenations and semihydrogenations, 9,[12][13][14] lactonization, 10 asymmetric arylations, 15 Buchwald-Hartwig aminations, 16 and cross-coupling reactions. 15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction. 11,17 For example, Cao et al investigated the use of NHC-stabilized Au nanocrystals as electrocatalysts for the reduction of CO2 to CO. Interestingly, the Au nanocrystal catalyst with surface-bound carbene ligands exhibited a higher Faradaic efficiency for CO2 reduction to CO than did bare (or ligand-less) Au nanoparticles; it was further shown that the NHC affected the mechanistic pathway of catalysis. 17 Despite the proven benefits of applying NHC ligands to nanocrystal catalysts, they have thus far only been supported on metal nanocrystal catalysts (e.g., Ru, Au, Pt, Pd, Cu).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation